Salmonella in Liquid Eggs and Other Foods in Fukuoka Prefecture, Japan - Koichi Murakami; Tamie Noda; Daisuke Onozuka; Nobuyuki Sera (International Journal of Microbiology)
The study aimed to evaluate the prevalence of Salmonella in retail and wholesale foods in Fukuoka Prefecture, Japan. A total of 2,021 samples collected between 1999 and 2010 were tested using a culture method. Samples consisted of liquid eggs (n=30), meat (beef and pork) (n=781), offal (n=69), processed meats (n=2), seafood (n=232), processed seafood (dried fish) (n=76), vegetables (n=481), processed vegetables (n=87), fruits (n=167), and herbs (n=96) from 574 outlets and wholesale agents in 15 areas (five samples were undocumented regarding outlets). Overall, liquid egg showed significantly (P<0.001) higher frequencies of Salmonella contamination (13.3%) than beef (1/423, 0.2%) and pork (3/235, 1.3%). Salmonella enterica subsp. enterica serovar Enteritidis, the most common serovar as a human pathogen, were isolated from two liquid egg samples. No Salmonella were isolated from seafood and vegetable-related samples including seed sprouts (n=261). In conclusion, liquid egg is a significant Salmonella vehicle, showing a need to continue the vaccination of chickens to prevent S. Enteritidis contamination in Japanese eggs. Moreover, further study is needed to evaluate Salmonella contamination in seed sprouts with more sampling from retailers there.